INFLUENCE OF STRUCTURAL PARAMETERS ON OPTICAL CHARACTERISTICS OF PHOTONIC CRYSTAL FIBERS WITH CIRCULAR LATTICE - Van Trong Dang; Tran Bao Tran Le; Van Lanh Chu; Thi Hong Phuong Nguyen; Nguyen Minh Hang Trang; Trong Duc Hoang; Thi Thuy Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
We demonstrate in this study that near-zero, ultra-flattened chromatic dispersion can be achieved over a wide range of wavelengths in photonic crystal fibers (PCFs) by means of slight variations in the geometrical parameters of the cladding. To do that, a new solid-core circular PCF design with various air hole diameters and lattice constants is presented, and the design features are numerically analyzed in detail. After 40 simulations, we determined three structures that possess optimal dispersion with the following lattice constants (Ʌ) and filling factors for the first ring (d1/Ʌ): Ʌ = 0.8 µm, d1/Ʌ = 0.45 for #F1, Ʌ = 0.9 µm, d1/Ʌ = 0.45 for #F2, and Ʌ = 1.0 µm, d1/Ʌ = 0.45 for #F3. High nonlinearity and low attenuation are outstanding features of our model. With these advantages, the proposed fibers are targeted for smooth flat broadband supercontinuum generation for near-infrared applications.